Analysis of the fragmentation function based on ATLAS data on proton-proton collisions at √s=7 TeV - Barba Moral, Elias (2016)
In high energy particle physics, the collision of two protons leads to quantum interactions through the strong force. This interactions produce highly energetic scattered particles that start to produce more particles forming collimated cones of particles, called jets. The phenomena that produces these jets from the scattered particles is called hadronization, and is explained using the fragmentation function. In this work, the fragmentation functions from with the PYTHIA Monte Carlo event generator and the data from the ATLAS experiment in various jet energy ranges and they were used to study a cascade model proposed by Richard Feymann and Richard Field. I found that PYTHIA is able to reproduce the ATLAS data with reasonable precision. The model results are presented using two diﬀerent kinds of data: one being the same as used by ATLAS, and another with higher granularity data. The Feynman model is able to describe the data within ranges of 20% for most of the jet energy ranges available. It is remarkable how the results obtained by applying the model to the ATLAS data agree with the results of the model with the PYTHIA simulation.